A histone-like protein of Helicobacter pylori protects DNA from stress damage and aids host colonization - Wang, Ge (2012)
Genomic DNA in a bacterial cell is folded into a compact structure called a nucleoid, and nucleoid-associated proteins are responsible for proper assembly of active higher-order genome structures. The human gastric pathogen Helicobacter pylori express a nucleoid-associated protein encoded by the hup gene, which is the homolog to the Escherichia coli histone-like protein HU. An H. pylori hup mutant strain (X47 hup:cat) showed a defect in stationary phase survival. The X47 hup:cat mutant was more sensitive to the DNA damaging agent mitomycin C, and displayed a decreased frequency of DNA recombination, indicating Hup plays a significant role in facilitating DNA recombinational repair. The X47 hup:cat mutant was also sensitive to both oxidative and acid stress, conditions that H. pylori commonly encounters in the host. The hup mutant cells survived significantly (7-fold) less upon exposure to macrophages than the wild type strain. In a mouse infection model, the hup mutant strain displayed a greatly reduced ability to colonize host stomachs. The geometric means of colonization number for the wild type and hup mutant were 6 × 10(5) and 1.5 × 10(4) CFU/g stomachs, respectively. Complementation of the hup strain by chromosomal insertion of a functional hup gene restored oxidative stress resistance, DNA transformation frequency, and mouse colonization ability to the wild type level. We directly demonstrated that the purified His-tagged H. pylori Hup protein can protect (in vitro) an H. pylori-derived DNA fragment from oxidative damage.